2009
DOI: 10.1111/j.1365-313x.2009.03989.x
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of MYB46 identifies transcriptional regulatory genes involved in secondary wall biosynthesis in Arabidopsis

Abstract: SUMMARYMYB46 functions as a transcriptional switch that turns on the genes necessary for secondary wall biosynthesis. Elucidating the transcriptional regulatory network immediately downstream of MYB46 is crucial to our understanding of the molecular and biochemical processes involved in the biosynthesis and deposition of secondary walls in plants. To gain insights into MYB46-mediated transcriptional regulation, we first established an inducible secondary wall thickening system in Arabidopsis by expressing MYB4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
290
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(300 citation statements)
references
References 65 publications
7
290
1
2
Order By: Relevance
“…Specifically, its overexpression affects the expression of several cell wall biosynthesis genes, although it does not influence secondary wall thickness, and dominant repression of its expression results in a reduction in secondary cell wall thickening (Ko et al, 2009;Zhong et al, 2008). Here, we demonstrated that AtMYB52 is involved in ABA response during postgermination growth.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Specifically, its overexpression affects the expression of several cell wall biosynthesis genes, although it does not influence secondary wall thickness, and dominant repression of its expression results in a reduction in secondary cell wall thickening (Ko et al, 2009;Zhong et al, 2008). Here, we demonstrated that AtMYB52 is involved in ABA response during postgermination growth.…”
Section: Discussionmentioning
confidence: 78%
“…For instance, MYB58 and MYB63 are regulators of lignin biosynthesis (Zhou et al, 2009), and MYB103, MYB85, MYB52 and MYB54 control secondary wall thickening (Zhong et al, 2008). Among the MYB transcription factors, hierarchical relationships exist, and it has been demonstrated that MYB52 is a downstream target of MY46, which is a master switch for secondary cell wall formation in Arabidopsis (Ko et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recently several studies have been reported that some of these transcription factors are downstream of the VND/NST/SND1 (Ko et al 2009;McCarthy et al 2009;Yamaguchi et al 2010aYamaguchi et al , 2010Zhong et al 2007aZhong et al , 2008Zhou et al 2009). Particularly, MYB46, MYB83, MYB103, and KNOTTED1-LIKE HOMEODOMAIN PROTEIN 7 (KNAT7) are direct targets of SND1/NST3/ANAC012 and possibly of NST1, VND6, and VND7 (Figure 3; Ko et al 2009;McCarthy et al 2009;Zhong et al 2007a). Overexpression of MYB46 or MYB83 activates gene expression of biosynthetic pathways of cellulose, hemicellulose and lignin and induces ectopic secondary wall formation (Ko et al 2009;McCarthy et al 2009;Zhong et al 2007a).…”
Section: Downstream Targets Of Vnd and Nst Proteinsmentioning
confidence: 99%
“…Two MYB genes, PtrMYB021 (30) and PtrMYB52 (Table S5), are present in second layer, and two NAC genes, PtrSND1-A2 and PtrVND6-C2 (30), are in the third layer. PtrMYB021 is the poplar ortholog of Arabidopsis AtMYB46, known to up-regulate AtLAC10 and other laccase genes through an eight-nucleotide core motif (RKTWGGTR) (31,32), further validating the GRN. We also found some genes with unknown functions in the GRN.…”
Section: Down-regulation Of Ptrlac Transcript Abundance By Overexpresmentioning
confidence: 99%